2002
DOI: 10.1007/s00204-002-0353-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the dithiocarbamate fungicide propineb in primary neuronal cell cultures and skeletal muscle cells of the rat

Abstract: After repeated-dose toxicity studies with the fungicide propineb, reversible effects on muscle functions were found. Therefore, mechanistic investigations should contribute to clarification of its mode of action in relation to disulfiram and diethyldithiocarbamate neurotoxicity or direct effects on muscle cells. In principle, besides the dithiocarbamate effects, two different mechanisms have been discussed for this fungicide. One mechanism is the degradation to carbon disulfide (CS(2)) and propylenthiourea (PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Well-known neurotoxicants like n-hexane, acrylamide and 3-nitropropionic acid have shown that the glycolysis plays a central role in aggravating neuropathies (Sabri et al 1979a(Sabri et al , 1979bSchmuck et al 2000). The same effects on the energy supply were seen with disulfiram, a thiocarbamate, and carbon disulfide (Schmuck et al 2002b).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Well-known neurotoxicants like n-hexane, acrylamide and 3-nitropropionic acid have shown that the glycolysis plays a central role in aggravating neuropathies (Sabri et al 1979a(Sabri et al , 1979bSchmuck et al 2000). The same effects on the energy supply were seen with disulfiram, a thiocarbamate, and carbon disulfide (Schmuck et al 2002b).…”
Section: Discussionsupporting
confidence: 52%
“…The amelioration of carbamate-induced effects on ATP production and glucose consumption by acetylcysteine may be related to a comparable mechanism. However, a reaction with SH-groups should be a slow process and may include metabolic degradation of the test compounds because GSH itself is not degraded within 1 h. This is the case with compounds inducing oxidative stress like paraquat and hydrogen peroxide, and therefore this alternative mechanism can also be excluded for carbamates (Ro¨hrdanz et al 2001;Schmuck et al 2002b).…”
Section: Discussionmentioning
confidence: 97%
“…Dithiocarbamates form lipophilic complexes with di- and trivalent metallic cations, bonding through the sulfur atoms [ 102 ]. They are non-specific in action, and it is difficult to identify a single mechanism for their neurotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Mixtures of these pesticides also showed significantly increased levels of alpha-synuclein, a major component of Lewy bodies that is a hallmark of neurodegenerative diseases such as PD and Alzheimer's disease (Jia, 2006). Although adverse effects of exposure to both endosulfan and zineb have been reported (Gupta, 1976;Zaidi et al, 1985;Seth et al, 1986;Guven et al, 1999;Vaccari et al, 1999;Schmuck et al, 2002), the biochemical mechanisms by which endosulfan and zineb cause neurotoxicity are still largely unknown. The current studies were designed to assess the cytotoxicity of endosulfan and zineb, alone and in combination, as well as to investigate the mechanism of pesticide-induced cell death (apoptosis and necrosis) in the SH-SY5Y cell line.…”
Section: Introductionmentioning
confidence: 99%